PELUANG DAN TANTANGAN PENDIDIKAN AGAMA ISLAM DI ERA KECERDASAN BUATAN (AI) - Ahmad Khoiri; Endi Suhendi; Dendra Wijaya Daerob; Muhammad Sakir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Artificial Intelligence (AI) has fundamentally transformed the landscape of education, including Islamic Religious Education (PAI). This article examines the opportunities and challenges of integrating AI into Islamic Religious Education in Indonesia. Through literature review and critical analysis, this paper identifies several significant opportunities, including personalized learning, democratization of access to quality Islamic education, effective digital dakwah media, enhanced teacher competency, and new horizons in Islamic knowledge research. Conversely, it also identifies serious challenges such as threats to spiritual values and morality, spread of deviant religious content, digital inequality, identity crisis among young Muslims, AI bias, and excessive technological dependence. This study proposes four strategic approaches: integrating AI based on Islamic values, strengthening digital and religious literacy, reinforcing the teacher's role as murabbi, and developing an Islamic AI ecosystem. The conclusion suggests that AI is not a threat to be feared, but an opportunity to be managed wisely with Islamic principles as the foundation, maintaining balance between technological advancement and the preservation of Islamic spiritual values in education.